Polylactic Acid Cellulose Nanocomposite Films Comprised of Wood and Tunicate CNCs Modified with Tannic Acid and Octadecylamine - Matthew J. Dunlop (MDPI AG, 2021)
Herein, a one-pot strategy was used to prepare hydrophobic cellulose nanocrystals (CNCs) surface-modified with tannic acid and octadecylamine. By this strategy, CNCs derived from wood (W-CNC) and tunicates (T-CNC) were modified in situ and incorporated into a polylactic acid (PLA) matrix using two methods, without first drying the CNCs. Films of PLA-CNC nanocomposites were prepared both by solution casting and by wet compounding in a thermo-kinetic mixer, followed by melt extrusion. Various properties of these PLA nanocomposites were evaluated herein, along with an assessment of how these properties vary with the type of CNC reinforcement. Cast films with a hybrid mixture of wood and tunicate CNCs displayed improved mechanical properties compared to either wood or tunicate CNCs, but extruded films did not show this hybrid effect. The water vapor permeability of the extruded nanocomposite films with 1% CNCs was reduced by as much as 60% compared to the PLA films. The composite films also showed enhanced biodegradation compared to neat PLA films. These results demonstrate that wet compounded PLA composites produced with wood or tunicate CNCs modified using a one-pot, water-based route have improved barrier and biodegradation properties, indicating a potential for packaging applications without having to dry the CNCs.